Global encounter. Rivarly between Islamic State and al-Qaeda over the supremacy of the global jihadist movement (Economic and Political Thought, 2015)
The aim of the article is the comparison of Islamic State and al-Qaeda,demonstrating similarities and differences between the two organisations. Themain hypothesis of the research is the assumption that the Islamic State isdifferent from al-Qaida primarily due to the fact that the main purpose of theorganisation activity is to establish an Islamic state based on Sharia principles.This assumption is part of the strategy established by the deceased spiritualleader of the group – Abu Mus’ab az-Zarqawi. Despite the fact that the finalstrategic goal of al-Qaeda is now convergent with that of the Islamic State,al-Qaeda’s methods of operation developed under the leadership of Osamabin Laden focused on the destabilisation of the West and the Muslim supportof liberation movements. In turn, the Islamic State focuses on the eliminationof apostate regimes in the Arab world and establishment of the Caliphate.Currently the diversity of perspectives of leaders of both terrorist organisations,despite many similarities in the ideological issues, has led to a rivalry betweenthe two factions for hegemony over the global jihadist movement.